Introduction to economics - Cairncross, Alec.; Sinclair, P. J. N. (London ; Boston : Butterworths, 1982)
This edition emphasized leading variables that do not lend themselves to mathematical specification and are usually more prominent in applied economics than in current economic theory
"Sources of British economic statistics": p. 453-455.
Includes bibliographical references and index.
ucj 17/01/2019
Loans
Keywords: Economics